2011
DOI: 10.1016/j.foreco.2010.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile growth of hybrid poplars on acidic boreal soil determined by environmental effects of soil preparation, vegetation control, and fertilization

Abstract: a b s t r a c tThe silviculture of hybrid poplars and other fast-growing tree species is a promising solution to reduce the pressure on natural forests while maintaining wood supplies to industries. However, hybrid poplars are very sensitive to competing vegetation and to inadequate soil conditions and fertility. Possible management tools include mechanical site preparation (MSP), vegetation control (VC), and fertilization. Experimental plantations of hybrid poplars (one clone, Populus balsamea × Populus maxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 74 publications
(82 reference statements)
3
29
0
Order By: Relevance
“…(i) To ensure that fast-growing trees can achieve their full potential without using herbicides, which are banned in Quebec in forestry operations, through employing site-preparation techniques such as trenching and mounding (Bilodeau-Gauthier et al 2011;Buitrago et al 2015). These techniques create a heterogeneous microtopography that could provide habitat for vascular understory plant species (Haeussler et al 1999;Ramovs and Roberts 2003), as well as hatching habitat for amphibians (Semlitsch et al 2009).…”
Section: Some Examples Of Novel Stand-level Managementmentioning
confidence: 99%
“…(i) To ensure that fast-growing trees can achieve their full potential without using herbicides, which are banned in Quebec in forestry operations, through employing site-preparation techniques such as trenching and mounding (Bilodeau-Gauthier et al 2011;Buitrago et al 2015). These techniques create a heterogeneous microtopography that could provide habitat for vascular understory plant species (Haeussler et al 1999;Ramovs and Roberts 2003), as well as hatching habitat for amphibians (Semlitsch et al 2009).…”
Section: Some Examples Of Novel Stand-level Managementmentioning
confidence: 99%
“…Bilodeau-Gauthier et al (2011) claimed that the use of weed control treatments for Populus typically led to an increase in the growth rate of the trees and consequently to possible modifications of wood quality. In Argentina, Monteoliva and Senisterra (2008) analysed 12 poplar clones (10-year-old Delta Gold) grown in the same location of this study; the authors found positive correlations between growth parameters and density.…”
Section: Growth Parameters and Wood Propertiesmentioning
confidence: 99%
“…The application of nitrogen (N) fertilizers and the control of herbaceous vegetation have received considerable attention as two different approaches that can enhance the growth rate and the productivity of forest plantations (Little et al 2003;Bilodeau-Gauthier et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Van den Driessche (1999) demonstrated that the application of fertilizers about 20 cm from the poplar cuttings enhanced growth compared to untreated cuttings and was about twice as effective as banding of fertilizers [12]. Similarly, Bilodeau-Gauthier (2011) found that the application of fertilizers applied to the base of a planted tree positively influenced its growth [13]. Since poplars are sensitive to competing vegetation [9,14,15] and fertilizing whole areas increases the growth of competing vegetation [16], the application of fertilizers directly to the transplant could be an alternative strategy for addition of extra nutrients at the time of planting.…”
Section: Introductionmentioning
confidence: 96%